A Protective Strategy to Counteract the Oxidative Stress Induced by Simulated Microgravity on H9C2 Cardiomyocytes. (20th April 2021) - Guarnieri, Simone; Morabito, Caterina; Bevere, Michele; Lanuti, Paola; Mariggiò, Maria A.
Abstract : Microgravity affects human cardiovascular function inducing heart rhythm disturbances and even cardiac atrophy. The mechanisms triggered by microgravity and the search for protection strategies are difficult to be investigated in vivo. This study is aimed at investigating the effects induced by simulated microgravity on a cardiomyocyte-like phenotype. The Random Positioning Machine (RPM), set in a CO2 incubator, was used to simulate microgravity, and H9C2 cell line was used as the cardiomyocyte-like model. H9C2 cells were exposed to simulated microgravity up to 96 h, showing a slower cell proliferation rate and lower metabolic activity in comparison to cell grown at earth gravity. In exposed cells, these effects were accompanied by increased levels of intracellular reactive oxygen species (ROS), cytosolic Ca 2+, and mitochondrial superoxide anion. Protein carbonyls, markers of protein oxidation, were significantly increased after the first 48 h of exposition in the RPM. In these conditions, the presence of an antioxidant, the N-acetylcysteine (NAC), counteracted the effects induced by the simulated microgravity. In conclusion, these data suggest that simulated microgravity triggers a concomitant increase of intracellular ROS and Ca 2+ levels and affects cell metabolic activity which in turn could be responsible for the slower proliferative rate. Nevertheless, the very low number of detectable dead cells and, more interestingly, the protective effect of NA, demonstrate that simulated microgravity does not have "an irreversible toxic effect" but, affecting the oxidative balance, results in a transient slowdown of proliferation.